1st Spring School of Acousto-Optics and its Applications Gdańsk–Wieiyea 26–30 May 1980 - ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1981)
The School was organized by the Institute of Physics of the University of Gdańsk and the Sections of Quantum and Molecular Acoustics and Sonochemistry of Polish Acoustical Society and supported by the Institute of Fundamental Technological Research of the Polish Academy of Sciences.